Sustainable Development : The Challenge of Transition - Schmandt, Jurgen; Ward, C. H. (Cambridge University Press, 2000)
Demographers predict that world population will double to around twelve billion people during the first half of the twenty-first century and then begin to level off. Based on this scenario, Sustainable Development: The Challenge of Transition examines what societal changes must occur over the next generation to ensure a successful transition to sustainability within the constraints of the natural environment. An array of prominent authors present a broad discussion of the dimensions of sustainable development: not just economic and environmental, but also spiritual and religious, corporate and social, scientific and political. Unlike other books on the subject, this volume provides insightful policy recommendations about how business, government, and individuals must change their values, priorities, and behaviour to meet these challenges. This volume will appeal to scholars and decision makers interested in global change, environmental policy, population growth, and sustainable development, and also to corporate environmental managers.